Intrapreneurship and trust - Niklas Elert; Erik Stam; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2019)
Trust and entrepreneurship are seen as key ingredients of long-term prosperity. However, it is not clear how these two are related. Part of the confusion can be traced back to the measurement of entrepreneurship, biased towards independent entrepreneurship (self-employed and new firms), and excluding entrepreneurship within established organizations. We shed new light on the relationship between trust and entrepreneurship, by proposing two mechanisms relating trust to entrepreneurship by employees, so-called intrapreneurship. We hypothesize that generalized trust influences the prevalence of intrapreneurship in an economy, and the allocation of entrepreneurial talents between independent entrepreneurship and intrapreneurship, through two mechanisms. First, generalized trust may substitute for complete contracts as a means of organizing labor in society, enabling a level of job autonomy in organizations necessary for intrapreneurship to flourish. Second, by way of its influence on the size and scope of the welfare state, generalized trust may increase the benefits of employment relative to self-employment, causing entrepreneurial individuals to elect to be intrapreneurs rather than independent entrepreneurs. Using a novel dataset, we find support for these hypotheses in a cross-country regression model covering the time period 2011-2017.
Keywords: H30; J20; J83; L26; M13; O12; O31; O43; O57; 330; Trust; Intrapreneurship; Entrepreneurship; Entrepreneurial behavior; Institutions; Job autonomy; Welfare state